Analysis of Students' Reading Strategies in Shaping Academic Success - Muhammad, Kemas; Irmansyah, Irmansyah; Febiola, Errine Vira (JURNAL IJ-ATL, 2023)
This study aims to analyze the reading strategies applied by students in shaping academic success. The approach used is qualitative with a case study design, where data were collected through interviews, observations, and documentation. Data were analyzed using thematic analysis techniques based on the Miles and Huberman model, which allows the identification of key themes related to the implementation of reading strategies. The results of the study indicate that effective reading strategies contribute significantly to improving students' academic achievement by encouraging active participation, improving reading comprehension skills, and building students' self-confidence. This study highlights the role of teachers in supporting the implementation of these strategies and the importance of technology in strengthening the effectiveness of reading strategies. The implications of this study suggest that optimizing reading strategies is critical to academic success, and the integration of technology can strengthen these strategies, creating a more inclusive and supportive learning environment.